2001
DOI: 10.3147/jsfp.36.139
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Infections Pancreatic Necrosis Virus(IPNV) from Leukocytes of Carrier Rainbow Trout Oncorhynchus mykiss.

Abstract: ABSTRACT--Blood and kidney leukocytes were purified from two-year-old rainbow trout carrying infectious pancreatic necrosis virus (IPNV) and the cells were processed to detect the virus by two methods: 1) indirect immunofluorescence stain followed by flow cytometry analysis, and 2) RT-PCR or nested-PCR amplification. These methods were compared with separate homogenization of visceral samples, followed by inoculation on cell cultures and seroneutralization, a procedure routinely employed by most disease diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 21 publications
0
18
1
Order By: Relevance
“…Both procedures are time‐consuming and rely on the use of cell cultures, but differences in sensitivity have been reported. Some authors have reported the detection of IPNV in rainbow trout leucocytes by flow cytometry (Rodriguez et al. 2001), but unfortunately this technology is not affordable for many laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Both procedures are time‐consuming and rely on the use of cell cultures, but differences in sensitivity have been reported. Some authors have reported the detection of IPNV in rainbow trout leucocytes by flow cytometry (Rodriguez et al. 2001), but unfortunately this technology is not affordable for many laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…The kidney seems to be an important organ for the uptake and expression of DNA vaccines since pDNA uptake and transgene expression have both been demonstrated in kidney macrophages from several fish species [27,31,32]. We previously demonstrated VP2 gene expression in the kidneys of brown trout 30 days post-vaccination when studying the innate immune response induced by the pcDNA-VP2 vaccine administered by injection [1]. Here we obtained similar results after oral delivery of the same plasmid, indicating that alginate microspheres are indeed good carriers for oral delivery.…”
Section: Vaccine Treatmentmentioning
confidence: 98%
“…IPNV VP2 protein expressed in BF-2 cells was detected with an indirect immunofluorescence assay (IFA), and the fluorescent cells were both quantified by flow cytometry [36] and observed by UV microscopy. Briefly, after incubation of transfected and non-transfected BF-2 cells at -20 C for 3 days, cell monolayers were disrupted with trypsin (0.25%), fixed with 3.7% formaldehyde in PBS for 15 min and permeabilized with 0.1% Triton X-100 in PBS for 1 min.…”
Section: Immunofluorescence Assaymentioning
confidence: 99%